Understanding the roles of PIWIL3 and TACC3 proteins during bovine oocyte development - Leitoguinho, Ana Rita Canhoto, 1989- (2013)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2012